2015
DOI: 10.1016/j.neuron.2015.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Logic of Pan-Neuronal Gene Expression in C. elegans

Abstract: While neuronal cell types display an astounding degree of phenotypic diversity, most if not all neuron types share a core panel of terminal features. However, little is known about how pan-neuronal expression patterns are genetically programmed. Through an extensive analysis of the cis-regulatory control regions of a battery of pan-neuronal C.elegans genes, including genes involved in synaptic vesicle biology and neuropeptide signaling, we define a common organizational principle in the regulation of pan-neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
196
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(224 citation statements)
references
References 46 publications
18
196
1
Order By: Relevance
“…We observed that both reporters were expressed in I4 and other MS-derived neurons (Figure 1F and unpublished data); observations by Stefanakis et al [11] similarly suggest that MS- and AB-derived neurons share basic neuronal molecular attributes. To determine whether I4 precursor cells express mesodermal characteristics, we examined the expression of an hlh-1 reporter during embryogenesis.…”
Section: Resultssupporting
confidence: 80%
“…We observed that both reporters were expressed in I4 and other MS-derived neurons (Figure 1F and unpublished data); observations by Stefanakis et al [11] similarly suggest that MS- and AB-derived neurons share basic neuronal molecular attributes. To determine whether I4 precursor cells express mesodermal characteristics, we examined the expression of an hlh-1 reporter during embryogenesis.…”
Section: Resultssupporting
confidence: 80%
“…In the absence of FLP expression, neither strain produced detectable levels of GFP in the nervous system ( Figure 4B and Figure S5). Upon pan-neuronal expression of FLP, both strains exhibited strong GFP expression throughout the nervous system, as expected since both of these genes are expressed in all neurons (Stefanakis et al 2015). We conclude that the FLP-on connectors permit recombination-dependent tag expression for both N-and C-terminal tags.…”
supporting
confidence: 73%
“…Because shn-1 is expressed in muscles (Stefanakis et al, 2015), we assayed EGL-19/Ca v 1 channel function by recording voltage-activated calcium currents in body muscle, using salines containing potassium channel blockers (TEA and 4AP). In these conditions, the remaining voltage-activated inward current is entirely blocked by the EGL-19 antagonist nemadipine (Lainé et al, 2011).…”
Section: Resultsmentioning
confidence: 99%